A Reduced Form of the Three Factor Commodity Derivative Valuation Model - Dibessa, Betiglu Mezgebu; Ngare, Philip; Orwa, George Otieno (Research India Publications, 2016)
This study build a reduced form of three factor valuation model by explicitly taking into account the unobservable character of the convenience yield. The spot priceprocess,theinstantaneousconvenienceyieldandCIRinterestrateprocessare taken in the reduced form of three factor valuation model. The CIR interest rate process prevents interest rate from being negative. We simulate the reduced form three factor valuation model by using Milstein and Euler discretization schemes. We study the performance of Milstein and Euler discretization schemes theoretically and empirically in reduced form three factor valuation model. The Milstein discretizationschemehasbetterapproximationthanEulerdiscretizationschemein reduced form three factor valuation model. As the time of maturity, T, is less and the time interval decreases the result obtained from the simulation of reduced form three factor valuation model for spot price process, convenience yield and interest rate process has better approximation
Keywords: Reduced Form Model; Discretization; Milstein scheme; Euler scheme